Colocar o sistema financeiro ao serviço dos pobres e das PME - Osman, Abdul Magid; Osman, Djamila Pontes (2020)
O esforço de inclusão financeira alcançou resultados positivos, tendo a bancarização da população moçambicana aumentado consideravelmente, em particular depois de 2011-12. Contudo, o impacto económico e social foi limitado, considerando que a produtividade agrícola se tem mantido baixa e os níveis de pobreza ainda são elevados. A doutrina neoliberal na esfera económica, a sua expressão nas políticas monetárias restritivas e a fraqueza do sistema de democracia multipartidária têm sido factores institucionais de constrangimento ao desenvolvimento económico e social. Consequentemente, este estudo propõe algumas medidas de reforma institucional para se expandir o crédito aos agricultores familiares de subsistência, às pequenas e médias empresas, à população em geral e às famílias de rendimento mais baixo em particular. Os jovens poderão beneficiar de créditos mais acessíveis para habitação. Os produtores familiares rurais também necessitam de um suporte sistémico público.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; financial inclusion / inclusão financeira; fiscal policy / política fiscal; monetary policy / política monetária; poverty / pobreza; private sector / setor privado; youth / juventude

Putting the financial system to work for the poor and SMEs - Osman, Abdul Magid; Osman, Djamila Pontes (2020)
Abstract: The financial inclusion effort achieved positive results, with the number of Mozambicans having access to banking services increasing considerably, particularly after 2011–12. However, the economic and social impact was limited, considering that farm productivity has remained low and poverty levels are still high. The neoliberal doctrine in the economic sphere, its expression in the restrictive monetary policies, and the weakness of the multi-party democracy system have been institutional factors restricting economic and social development. Consequently, this study proposes some institutional reform measures to expand credit to family subsistence farmers, small and medium-sized enterprises, the population in general, and low-income families in particular. Young people could benefit from more accessible housing loans. Rural family farmers also need systemic, public support.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; financial inclusion / inclusão financeira; fiscal policy / política fiscal; monetary policy / política monetária; poverty / pobreza; private sector / setor privado; youth / juventude

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado